(untitled) (Emancipação, 2022)
This article aimed to give a brief panorama concerning the public ATER course, highlighting the characteristics of the current assistance given to Northeastern family farmers. To do so, it was reviewed part of the literature on the subject and it was analyzed the information extracted from the 2017 IBGE Agricultural Census, the Annual Budget Law (LOA) and the Annual Activity Reports carried out by public ATER agencies in the states of Alagoas, Sergipe, Piauí, Pernambuco and Rio Grande do Norte, in the year of 2020. Analyzing LOA data, it is highlighted the budget drop and recent dismantling of several achievements implemented before the 2016 policy changes. Besides, census data show that more than 90% of family farmers in the Northeast declared that they did not have access to ATER services in 2017. Considering what was mentioned above, it is concluded that in terms of budget, personnel and infrastructure the public ATER needs restructuring and strengthening.